2013
DOI: 10.5152/dir.2013.13106
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of placenta with relative apparent diffusion coefficient and relative T2 signal intensity analysis

Abstract: ORIGINAL ARTICLE PURPOSE We aimed to test the null hypothesis that relative apparent diffusion coefficient (rADC) and relative signal intensity values (rSI HASTE ) do not change in the evaluation of placental maturation with advancing gestational age. MATERIALS AND METHODSFifty-six fetuses with diffusion-weighted magnetic resonance imaging (DW-MRI) data were enrolled in this retrospective study. Fetuses were analyzed in three different gestational age groups: group 1, 18-23 weeks; group 2, 24-28 weeks; and g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
28
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(32 citation statements)
references
References 14 publications
(20 reference statements)
3
28
1
Order By: Relevance
“…With the aid of SPEN, ADC values could be measured for mouse placenta; these fell in the ∼2.9 ± 0.9 × 10 −3 mm 2 /s range, slightly higher but comparable in dispersion to the 0.5-2.5 × 10 −3 mm 2 /s range that was previously reported for human placentas (16,37) and larger than the average ADC = 0.9 ± 0.3 reported for rats (19). The first of these studies also revealed a decrease in placental ADCs from 2.2 to 0.7 × 10 −3 mm 2 /s in humans over the course of weeks 20-40 of gestation if a b = 0 value was included in the ADC measurement, but no statistically significant progression if b ≥ 50 s/mm 2 was the initial point-presumably due to the filtering out of perfusion effects.…”
Section: Resolving Subvoxel Placental Structures Using a Multicomponentsupporting
confidence: 70%
“…With the aid of SPEN, ADC values could be measured for mouse placenta; these fell in the ∼2.9 ± 0.9 × 10 −3 mm 2 /s range, slightly higher but comparable in dispersion to the 0.5-2.5 × 10 −3 mm 2 /s range that was previously reported for human placentas (16,37) and larger than the average ADC = 0.9 ± 0.3 reported for rats (19). The first of these studies also revealed a decrease in placental ADCs from 2.2 to 0.7 × 10 −3 mm 2 /s in humans over the course of weeks 20-40 of gestation if a b = 0 value was included in the ADC measurement, but no statistically significant progression if b ≥ 50 s/mm 2 was the initial point-presumably due to the filtering out of perfusion effects.…”
Section: Resolving Subvoxel Placental Structures Using a Multicomponentsupporting
confidence: 70%
“…Such outcomes support that maternal stress early in pregnancy promotes a delay in the maturation of the placenta through its effects on OGT, such as by altered epigenetic regulation of key developmental genes by OGT, O-GlcNAc, and its coregulators, including regulation of the recently identified demethylases, Tet1 and Tet2 (13,18,19). Delayed placental maturation has been associated with various clinical complications, including placental insufficiency (20), and has also been associated with altered neurodevelopment (21). This may be an evolutionary advantage whereby growth and development are delayed because of a less favorable environment.…”
Section: Discussionmentioning
confidence: 98%
“…A subsequent study [3] of singleton placental DWI used a correction factor for calculating ADC maps in order to minimize the relativity of the ADC measurement, which may be attributed to different biological and technical factors (e.g., body temperature and b value). The relative ADC (rADC) was calculated as ADC of the placenta divided by ADC of the globe, and it did not differ between GA groups.…”
Section: Introductionmentioning
confidence: 99%
“…Throughout pregnancy, several variations in the placenta occur that might produce restriction in the diffusion of water molecules and therefore has the capability for detection of placental changes and maturation [1,2,3]. …”
Section: Introductionmentioning
confidence: 99%